In quest of quasars; an introduction to stars and starlike objects - Bova, Ben, 1932- ([New York] Crowell-Collier Press, 1969)
Defines quasars and what they reveal about the nature of the universe.
Bibliography: p. 190-192.
Keywords: Quasars; Stars; Quasars; Stars